Nature in the city Bengaluru in the past, present, and future - Nagendra, Harini (Oxford University Press, 2016)
in a rapidly urbanizing India, what is the future of nature conservation? How does the march of development impact the conflict between nature and people in India’s cities? Exploring these questions, Nature in the City examines the past, present and future of nature in Bengaluru, one of India’s largest and fastest growing cities. Once known as the Garden City of India, Bengaluru’s tree-lined avenues, historic parks and expansive water bodies have witnessed immense degradation and destruction in recent years, but have also shown remarkable tenacity for survival. This book charts Bengaluru’s journey from the early settlements in the 6th century CE to the 21st century city and demonstrates how nature has looked and behaved and has been perceived in Bengaluru’s home gardens, slums, streets, parks, sacred spaces and lakes. A fascinating narrative of the changing role and state of nature in the midst of urban sprawl and integrating research with stories of people and places, this book presents an accessible and informative story of a city where nature thrives and strives.
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Natural history -- India -- Bangalore; Urban ecology (Biology) -- India -- Bangalore; Urban ecology (Sociology) -- India -- Bangalore; Nature conservation -- India -- Bangalore; Naturschutz; Stadtökologie; Indien; Bangalore